2018
DOI: 10.1002/jia2.25031
|View full text |Cite
|
Sign up to set email alerts
|

Increased non‐AIDS mortality among persons with AIDS‐defining events after antiretroviral therapy initiation

Abstract: Introduction HIV‐1 infection leads to chronic inflammation and to an increased risk of non‐AIDS mortality. Our objective was to determine whether AIDS‐defining events (ADEs) were associated with increased overall and cause‐specific non‐AIDS related mortality after antiretroviral therapy (ART) initiation.MethodsWe included HIV treatment‐naïve adults from the Antiretroviral Therapy Cohort Collaboration (ART‐CC) who initiated ART from 1996 to 2014. Causes of death were assigned using the Coding Causes of Death in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 39 publications
(56 reference statements)
7
38
1
1
Order By: Relevance
“…In our study, the prevalence of ADE in HIV/AIDS patients at ART initiation was 16.86%, which is roughly consistent with the data of previous studies in other countries or regions; for example, a report from Japan showed that 29.4% of patients with newly diagnosed HIV were ADE [29] . Our study also showed that even when individuals were on ART, the mortality of patients with ADE was significantly higher than that of those without ADE, which is consistent with a previous study [30] . In our study, disseminated mycosis, recurrent severe bacterial pneumonia, herpes zoster, extrapulmonary tuberculosis, and candidiasis of the oesophagus were the top causes of death by ADE.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the prevalence of ADE in HIV/AIDS patients at ART initiation was 16.86%, which is roughly consistent with the data of previous studies in other countries or regions; for example, a report from Japan showed that 29.4% of patients with newly diagnosed HIV were ADE [29] . Our study also showed that even when individuals were on ART, the mortality of patients with ADE was significantly higher than that of those without ADE, which is consistent with a previous study [30] . In our study, disseminated mycosis, recurrent severe bacterial pneumonia, herpes zoster, extrapulmonary tuberculosis, and candidiasis of the oesophagus were the top causes of death by ADE.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the prevalence of ADE in HIV/AIDS patients at ART initiation was 16.86%, which was roughly consistent with the data of previous studies in other countries or regions; for example, a report from France showed that 16% of patients with newly diagnosed HIV were ADE [31]. Our study also showed that even when individuals were on ART, the mortality of patients with ADE was signi cantly higher than that of those without ADE, which was consistent with some previous studies: a large multi-centre cohort study showed that non-AIDS mortality was twice as high among patients with an ADE compared to without an ADE [32], and this multiple is a little higher than that of this study; a research showed that HIV controllers experience non-ADE, albeit at lower rates than patients who do not spontaneously control the virus [33]. While in this study, disseminated mycosis, recurrent severe bacterial pneumonia, herpes zoster, extrapulmonary tuberculosis, and candidiasis of the oesophagus were the top causes of death by ADE.…”
Section: Discussionsupporting
confidence: 92%
“…Another important aspect of this study was investigating the occurrence of different types of events among HIV positive patients at the presence of each other. Recently, Pettit et.al [48]. showed that the risk of non-AIDS mortality among patients with an AIDS-defining event was twice higher than patients without an AIDS-defining event.…”
Section: Discussionmentioning
confidence: 99%